IMPLEMENTASI ASAS TANGGUNG JAWAB NEGARA SEBAGAI BENTUK PERLINDUNGAN HUKUM TERHADAP KERUSAKAN TERUMBU KARANG (Studi Kasus Kecelakaan Kapal MV Caledonian Sky di Raja Ampat) - Kristwan Genova Damanik (Law Review, 2018)
In Law No.32/2009 on Environmental Protection and Management, the principle of state responsibility is one of the means of protecting pollution and/or environmental damage. The principle of state responsibility server to ensure the utilization of natural resources for the welfare of the people, both present and future generations.Normatively, laws and regulations regulate sanctions for perpetrators of environmental violations, but in the application of law there is unity of action (ego sectoral), so the dispute resolution becomes complicated. Inadequate legal understanding of the state’s affirmative officials results  in  constrained law enforcement, and well as regulated legal sanctions for officials who neglect to carry out the task of giving the impression the government is not serious about addressing environment violations.The various  weaknesses and obstacles in applying the principle of state responsibility in the environmental law system in Indonesia related to ship MV Caledonian Sky  accident is the core of research that poured  in this paper